2011
DOI: 10.1073/pnas.1103581108
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial flow influences direction of tumor cell migration through competing mechanisms

Abstract: Interstitial flow is the convective transport of fluid through tissue extracellular matrix. This creeping fluid flow has been shown to affect the morphology and migration of cells such as fibroblasts, cancer cells, endothelial cells, and mesenchymal stem cells. A microfluidic cell culture system was designed to apply stable pressure gradients and fluid flow and allow direct visualization of transient responses of cells seeded in a 3D collagen type I scaffold. We used this system to examine the effects of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
450
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 432 publications
(467 citation statements)
references
References 42 publications
12
450
5
Order By: Relevance
“…In particular, adhesions containing paxillin elongate under applied traction (23). FAK also becomes autophosphorylated at Tyr 397 through binding with β1 integrins in endothelial cells in response to shear stress (24) and in breast adenocarcinoma cells when exposed to 3 μm/s IF as we have shown previously (17). Furthermore, phosphorylation of FAK at Tyr 397 is required for invadopodia formation for breast cancer cells (25), and FAK PY397 is differentially expressed in metastatic cervical carcinoma relative to noncancerous epithelium (26).…”
Section: Significancementioning
confidence: 69%
See 3 more Smart Citations
“…In particular, adhesions containing paxillin elongate under applied traction (23). FAK also becomes autophosphorylated at Tyr 397 through binding with β1 integrins in endothelial cells in response to shear stress (24) and in breast adenocarcinoma cells when exposed to 3 μm/s IF as we have shown previously (17). Furthermore, phosphorylation of FAK at Tyr 397 is required for invadopodia formation for breast cancer cells (25), and FAK PY397 is differentially expressed in metastatic cervical carcinoma relative to noncancerous epithelium (26).…”
Section: Significancementioning
confidence: 69%
“…In addition to imparting fluid stresses, IF convects autocrine factors downstream, causing gradients of autologously secreted chemokines that have been shown to direct migration downstream in response to IF (14). Furthermore, we have shown previously that at high cell densities, autocrine chemokine fields overlap with fields from neighboring cells, reducing transcellular autocrine gradients and inducing preferential upstream migration (17). In this study, cells were seeded at a sufficiently high density (6 × 10 5 cells per mL) and flow rate to minimize contributions from autocrine gradients, leading to upstream migration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several studies using microfluidic platform have been reported that recreate the 3D context of each aspect of the TME and metastasis in vitro. [10][11][12][13] However, to our knowledge, no versatile in vitro experimental model that reconstitutes direct interplay between constituents of the TME during tumorigenesis has yet been reported. Here we describe a biomimetic TME model to mimic the complex inter actions of the tumor, stromal, and endothe lial cells, all of which are essential components of the TME that hinder the effective treatment of cancers.…”
mentioning
confidence: 99%